Ways of Verbalizing the Emotion of Fear in Literary Works - Absamatova Shohida Baxtiyor qizi (Periodica Journal, 2023)
The relevance of this article is explained by the fact that, despite the constant interest of scientists, the emotion of fear has not yet received a complete linguistic description. Existing research in this area is rather fragmentary and focuses mainly on certain linguistic features of the expression of this emotion
Keywords: linguistics; fear; emotionalization